Importance of weather forecast in agriculture - Prakash, Ved; Kumar, Rakesh; Kumar Singh, Anil (Indian Farming, 2022)
Farmers obtain the highest output and improve their livelihood within the main limitation i.e. dependence on rainfed agriculture, thus having access to weather forecast information is very important. There is an urgent need for a meterological report that is easily accessible and understandable to farmers. The delivery of weather information should be a key factor in all agricultural policies and discussions in enhancing farm risk management. As complexities of agricultural systems and uncertainties of climate forecasts recommended that a coordinated effort is needed, if this technology is to be routinely used in agriculture in future. Weather information should be given by agro-meteorological stations one or two month before the onset of the rainy season that can allow farmers to change critical decisions i.e. sowing schedule, crop varieties, cropping ratio, intensification of production, allocation of labour and capital. Moreover, weather information forecasted by agro-meteorologists can support a smart fertilizer subsidy programme as well as smart improved seed programme.